(3dbWI GdYLdGf GdedNU ef hajGJ GdCYjGf dGHf NdcGfs - (3JGL GdOjf CHi GdeMGSf YHO GdHGbi Hf YHO GdeLjO GdjeGfis; (3GHf NdcGf , CMeO Hf eMeO Hf EHQGgje Hf CHj HcQ GdHQecj GdGQHdj, TeS GdOjf CHh GdYHGS,J (B681 (3g` s ((3GdbOS GdTQja s)
(3ChdgG (B:s
(3Ef Chdi eG GSJaJM Hg cJGH hGSJfLM Hg NWGH MeO Gddg Gdedc GdhgGH CeG HYO aEf Gdeff GdEdgjI hGdefM GdQHGfjI s
(3BNQgG (B:s
(3BNQ JQLeI ajg (B: (3JQLeI CHj GdaVd jhfS Hf eMeO Hf efYI hJfJgi gPg GdJQLeI ai U` (B193 (3hHYO Pdc JHOC GdRjGOI Ydi hajGJ GdCYjGf hChdgG JQLeI GHf NdcGf faSg hBNQgG JQLeI CHj YHO Gddg eMeO Hf eMeO fLe GdOjf GdWHQi GdTGaYi s
(3Cdag HGdeOjfI GdefhQI SfI (B729 (3HETGQI GdMGaX Yaja GdOjf GdeWQi Ke RGO YOI JQGLe hLOgG YfO GdeWQi HLeGYI de jPcQge GHf NdcGf hLeGYI HYO ReJgs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HNW Hg VHW s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3GdJGQjNs